Region- and Age-Dependent Alterations of Glial-Neuronal Metabolic Interactions Correlate with CNS Pathology in a Mouse Model of Globoid Cell Leukodystrophy. Issue 7 (July 2013) - Meisingset, Tore Wergeland; Ricca, Alessandra; Neri, Margherita; Sonnewald, Ursula; Gritti, Angela
Globoid cell leukodystrophy (GLD) or Krabbe disease is a lysosomal storage disorder caused by genetic defects in the expression and activity of galactosylceramidase, a key enzyme in the catabolism of myelin-enriched sphingolipids. While there are several histologic, biochemical, and functional studies on GLD, correlations between morphologic and biochemical alterations in central nervous system (CNS) tissues during disease progression are lacking. Here, we combined immunohistochemistry and metabolic analysis using 1 H and 13 C magnetic resonance (MR) spectra of spinal cord, cerebellum, and forebrain to investigate glial-neuronal metabolic interactions and dysfunction in a GLD murine model that recapitulates the human pathology. In order to assess the temporal- and region-dependent disease progression and the potential metabolic correlates, we investigated CNS tissues at mildly symptomatic and fully symptomatic stages of the disease. When compared with age-matched controls, GLD mice showed glucose hypometabolism, alterations in neurotransmitter content, N-acetylaspartate, N-acetylaspartylglutamate, and osmolytes levels. Notably, age- and region-dependent patterns of metabolic disturbances were in close agreement with the progression of astrogliosis, microglia activation, apoptosis, and neurodegeneration. We suggest that MR spectroscopy could be used in vivo to monitor disease progression, as well as ex vivo and in vivo to provide criteria for the outcome of experimental therapies.